Reactivation, Retrieval, Replay and Reconsolidation in and Out of Sleep: Connecting the Dots - Sara, Susan J. (Frontiers in Behavioral Neuroscience, 2010)
The neurobiology of memory has taken on a new look over the past decade. Re-discovery of cue-dependent amnesia, wide availability of functional imaging tools and increased dialogue among clinicians, cognitive psychologists, behavioral neuroscientists and neurobiologists have provided impetus for the search for new paradigms for the study of memory. Memory is increasingly viewed as an open-ended process, with retrieval being recognized as an intricate part of the encoding process. New memories are always made on the background of past experience, so that every consolidation is, in fact reconsolidation. serving to update and strengthen memories after retrieval. Spontaneous reactivation of memory circuits occurs during sleep and there is converging evidence from rodent and human studies that this is an important part of the extended off-line memory processing. The noradrenergic neuromodulatory system is engaged at retrieval, facilitating recall. The noradrenergic system is activated during sleep after learning and noradrenergic neurons fire in concert with cortical oscillations that are associated with reactivation of memory circuits. We suggest that the noradrenergic system and perhaps other neuromodulatory systems,[...]